The Application of Tannic Acid in Orthopedics - Sun, Yingchuan; Qu, Yang; Zhao, Jianwu (Frontiers in Materials, 2022)
Tannic acid (TA) is a naturally occurring polyphenol compound commonly found in tea, wine, and fruits. Because of the excellent structural and functional properties afforded by TA, materials based on the structure of polyhydroxyphenols have great value, particularly for orthopedic transplantation. This compound, for example, can form a strong interaction with metals and can form a stable coating on their surfaces, thus improving the physical and chemical properties of bone-implant surfaces and boosting implantation success rates. TA can also inhibit the activity of osteoclasts, thus playing a potential role in the treatment of osteoporosis. Furthermore, if the body becomes polluted with heavy metals, TA can chelate the ions to protect bone morphology and structure. It also has a significant antibacterial effect and can reduce infections caused by surgical implantation and inhibit a variety of tumor cells, thereby promoting its potential application in spinal metastasis surgery. Furthermore, it can also slow the corrosion caused by magnesium alloys, thereby greatly improving the development of degradable orthopedic metal fixatives. Importantly, TA is cheap and easy to obtain, making it extremely valuable for use in orthopedics. This review focuses on the research status and practical applications of TA, and prospects for its future application for orthopedics .